Knowing the People Oriented Character of Department Leaders with the Belbin Method - Murtasiyah; Muslimin Sanafi (Indonesian Journal of Advanced Research, 2023)
This study aims to analyze and understand the dominant character of department heads at PT BTU, who so far have appointed departmental leaders who prefer criteria of general technical competence, experience and soft skills such as communication skills, integrity, creativity, etc. According to Belbin, a person's character can be divided into 3 groups, namely the Thinking Oriented group consisting of Plant (PL), Monitor Evaluator (ME) and Specialist (SP). The Action Oriented group consists of Sharper (SH), Implementer (IMP) and Completer Finisher (CF). Finally, the People Oriented group consists of Team Workers (TW), Resource Investigators (RI) and Coordinators (C). From the research results for the 15 Departments at PT BTU, it was found that 73% of the leaders were People Oriented, and 27% were Action Oriented, and no Thinking Oriented dominant leaders. In order for the team in the department to further improve their performance, it is better if the deficiencies or weaknesses in one of the characters or orientations can be filled by staff who stand out in characters that the leader does not have.